Formation and functioning regularities of temple and monastery landscapes - Mishchenko, Olena V. (Institute of Geography Slovak Academy of Sciences, 2022)
Temple and monastery landscapes are natural and anthropogenic systems the markers of which are religious buildings such as church, monastery, cathedral, chapel, etc. The present research uses a transdisciplinary approach, which provides a scientific method within the sacred geography using the methodological approaches of other sciences, including philosophy, culturology, architecture and others. Regional physical and geographical, ideological, confessional factors determine the place of formation and functioning of temple and monastery landscapes in the structure of settlements. Among the leading geographical patterns of formation of temple and monastery landscapes are: orographic, the presence of contrasting environments and natural water bodies. According to the city zoning plan (Ukraine), temple and monastery landscapes are located in the area of religious and ceremonial buildings. However, often such territorial systems occur in the recreational area of active recreation, the area of promising green areas of public use (parks, squares, memorial parks) and even the area of apartment buildings, which is somewhat inconsistent with traditional canons of formation of sacred buildings. The analysis of Lutsk city monasteries (Volyn region, Ukraine) shows the formation of modern "accidental" buildings near them, which distorts the historical, cultural and sacred significance of the cult building.
Keywords: sacred landscape; temple and monastery landscape; regularities of formation of temple and monastery landscapes